Gemini-2.5-Flash Failure Rates on Edge-Case Coding Tasks Under Five-Nines Reliability Standards - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 1 peer-reviewed paper addressing the following research question: What is the failure rate of Gemini-2.5-Flash on edge-case coding tasks when evaluated for five-nines reliability standards. 8 claims were extracted from source literature; 7 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.2/10. This report is a machine-generated literature synthesis and does not constitute original r
Machine-generated literature synthesis.